Exploring the biological function of dreaming: lessons learned from recruitment challenges in a pilot study with PCA stroke patients - Fischmann, Tamara; Peters, Luisa; Rieker, Vanessa; Koslowski, Michael (Frontiers in Sleep, 2025)
BackgroundThis methodological report draws conclusions about a study that aimed to investigate the biological function of dreams. The main hypothesis in the study posited that dreams serve to maintain sleep by hallucinatory wish fulfillment in response to affect-laden impulses. A secondary hypothesis was whether dreams contribute to the consolidation of non-declarative memory. Neurological patients with ischemic stroke of the posterior cerebral artery (PCA stroke) served as a pragmatic lesion model for loss of dreaming ability, following evidence on the importance of parieto-occipital cortical areas for dream formation.MethodsThis quasi-experimental, two-arm controlled study intended to assess sleep quality and non-verbal memory consolidation in participants with PCA stroke who lost dreaming ability, compared to PCA stroke patients with preserved dreaming. Descriptive statistics using morbidity variables (e.g., NIHSS, Barthel-Index, and thrombolysis) were conducted to assess recruitment challenges.ResultsRecruitment was significantly constrained due to inclusion criteria and multimorbidity of the study population. Of 255 patients screened, 14 were included, and 6 completed the study. Descriptive data from the 14 inclusions as well as reasons for exclusion and dropouts are reported. Morbidity variables varied substantially between completers and non-completers, indicating that PCA stroke might not be an appropriate lesion model for dream research.ConclusionThis methodological report highlights the difficulties in recruiting adequate patient samples for dream research within a stroke lesion model, in order to gain valuable insights into methodological obstacles in this field. Solutions to these challenges are proposed, e.g., using functional lesion models in healthy controls with transcranial alternating current stimulation (tACS).Trial registrationclinicaltrials.gov (ID: NCT04749992).